The Effect of Progesterone Therapy in Severe Traumatic Brain Injury Patients on Serum Levels of s-100β, Interleukin 6, and Aquaporin-4 - Mahyudanil, Mahyudanil; Bajamal, A. H.; Sembiring, R. J.; Dharmajaya, R. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Severe TBI is leading in death and disability worldwide. The initial stage resulted from direct tissue damage and impaired autoregulation of cerebral blood flow. The level of S-100β, IL-6 and AQ4 in CSF increased in neuronal injury and BBB damage. PROG effect is assessed on biomarkers of S-100β, IL-6, and AQP4. AIM: The study examined the 1st to 4th day of progesterone administration. METHODS: The sample consisted of 23 participants in the control group and 16 participants in the treated group. Patients with GCS 4–8, not surgical, aged 15-50 years, coming in the first 24 h and patient’s family agreed to this research are included. The sample was taken from the serum, and the biomarker processed using ELISA. GOS 3 months used as prognostic. RESULTS: The result showed the mean value serum level of S100β, AQP4, and IL-6 increased on 24 h and 96 h after given PROG. Change of mean value of S100β day to day was 44.75 (96 h)–40.57 (24 h) – 4.18. In control group, change of S100β decrease to 42.51 (96 h)–46.11 (24 h) = −3.60, showing effect still unclearly proven in repairing neuronal injury, BBB disruption or another consideration on concentration of S100β, AQP4, and IL-6 in serum. CONCLUSION: S-100β serum levels is significant to predict outcome of severe TBI. Progesterone still unclearly proven in repairing neuronal injury and/or BBB disruption. Another consideration is temporal trajectory of S100β, AQP4, and IL-6. In future study, natural endogenous PROG should be sought. S-100β in future pharmaceutical trials may be possible as pharmacological target.